MAXIMUM VERSORIA-CRITERION (MVC)-BASED ADAPTIVE FILTERING METHOD FOR MITIGATING ACOUSTIC FEEDBACK IN HEARING-AID DEVICES - Akhtar, Muhammad Tahir; Albu, Felix; Nishihara, Akinori (Elsevier Ltd, 2021)
In any digital hearing aid (HAid), the input microphone and the receiver loudspeaker are closely located. Furthermore, HAid cannot be tightly fitted for comfort reasons. Therefore, it is almost impossible to avoid the acoustic feedback present due to the leakage path between the receiver loudspeaker and the input microphone. This paper investigates acoustic feedback cancellation (AFC) by developing a hybrid adaptive filtering approach. It is proposed to use two simultaneously adapted adaptive filters as in the previous method. The adaptation algorithms are based on a delay-based normalized least mean square (NLMS) algorithm. Furthermore, gradient information from a maximum Versoria-criterion (MVC)-based algorithm is also incorporated in the proposed approach. The effectiveness of this approach is demonstrated through extensive computer simulations.
Keywords: Type of access: Open Access; Acoustic feedback cancellation; Adaptive filtering; Hearing aids; Maximum Versoria-criterion; Modeling signal; NLMS algorithm; Research Subject Categories::TECHNOLOGY